Building Capacity for Prevention of Gender-Based Violence in the School Context - Ajduković, Dean; Car, Ivana; Päivinen, Helena; Sala-Bubaré, Anna; Vall, Berta; Husso, Marita (Frontiers in Psychology, 2021)
School-related gender-based violence (SRGBV) is highly prevalent worldwide which calls for a range of early prevention and innovative solutions. The presence of GBV in the school context is well documented and it highlights the importance of building competencies of teachers and other school professionals for recognizing and intervening in SRGBV cases. This paper analyses the current and future teachers’ training needs, and their level of preparedness for detecting and intervening in cases of GBV in the school context, with the objective of developing a targeted training program. The participants in this study were 597 current and future teachers and other school professionals from Croatia, Finland, and Spain. An ad-hoc built questionnaire was distributed in the three participating countries. Results show that the interest in receiving training is related to the perceived importance of coping with GBV in the (future) work and that the main topics of the training should focus on addressing parties of SRGBV, guidelines for prevention and intervention in schools as well as online GBV. These findings were similar in three countries and they provided user-generated topics and tools that served as a guideline for the development of a training program that aims to increase the knowledge about SRGBV and to develop skills for coping with GBV in the school context regarding victims, bystanders and perpetrators.